Using the learning alliance approach to develop national and sub national policies e.g climate change guidelines for the Ministry of Agriculture, Animal Industry and Fisheries - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The PACCA project used the learning alliance concept to encourage more inclusive and participatory policy making processes within east Africa countries at national and sub national levels. A number of national processes were influenced including, the development of the climate mainstreaming guidelines and review of the agriculture sector strategic plan. The project also provided research and a platform that led to the developing of two ordinances in Mbale district designed to help local coffee growers achieve greater production.